Superparamagnetic Nanoparticle Clusters for Cancer Theranostics Combining Magnetic Resonance Imaging and Hyperthermia Treatment - Hayashi, Koichiro (Ivyspring International Publisher, 2013)
Superparamagnetic nanoparticles (SPIONs) could enable cancer theranostics if magnetic resonance imaging (MRI) and magnetic hyperthermia treatment (MHT) were combined. However, the particle size of SPIONs is smaller than the pores of fenestrated capillaries in normal tissues because superparamagnetism is expressed only at a particle size <10 nm. Therefore, SPIONs leak from the capillaries of normal tissues, resulting in low accumulation in tumors. Furthermore, MHT studies have been conducted in an impractical way: direct injection of magnetic materials into tumor and application of hazardous alternating current (AC) magnetic fields. To accomplish effective enhancement of MRI contrast agents in tumors and inhibition of tumor growth by MHT with intravenous injection and a safe AC magnetic field, we clustered SPIONs not only to prevent their leakage from fenestrated capillaries in normal tissues, but also for increasing their relaxivity and the specific absorption rate. We modified the clusters with folic acid (FA) and polyethylene glycol (PEG) to promote their accumulation in tumors. SPION clustering and cluster modification with FA and PEG were achieved simultaneously via the thiol-ene click reaction. Twenty-four hours after intravenous injection of FA- and PEG-modified SPION nanoclusters (FA-PEG-SPION NCs), they accumulated locally in cancer (not necrotic) tissues within the tumor and enhanced the MRI contrast. Furthermore, 24 h after intravenous injection of the NCs, the mice were placed in an AC magnetic field with H = 8 kA/m and f = 230 kHz (Hf = 1.8×10(9) A/m∙s) for 20 min. The tumors of the mice underwent local heating by application of an AC magnetic field. The temperature of the tumor was higher than the surrounding tissues by ≈6°C at 20 min after treatment. Thirty-five days after treatment, the tumor volume of treated mice was one-tenth that of the control mice. Furthermore, the treated mice were alive after 12 weeks; control mice died up to 8 weeks after treatment.